(untitled) (GIST – Education and Learning Research Journal, 2011)
This study explores how a genre-based approach to writing instruction influenced by both genre theory and systemic functional linguistics supported the academic writing development of English language learners (ELLs) transitioning to middle school. Drawing on Systemic Functional Linguistics (SFL) as a tool for pedagogy and linguistic analysis, the teacher-researcher analyzed three instantiations of texts composed by ELLs to determine changes in the register of their texts during the course of genre-based writing pedagogy. Methods were qualitative in nature, involving both analysis of the text and the surrounding context of composition. Data came from multiple sources. They included videotaped observations of classroom interactions, transcriptions of semi-structured interviews with the student, collection of lesson plans, and materials used in lesson implementation, and field notes made by the participant observer. Findings suggest that a genre-based approach to writing instruction supported ELLs in producing texts that more closely approximated the register of the target genre.